2008
DOI: 10.2174/156802608783790983
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization of Engineered Tissues: Approaches to Promote Angiogenesis in Biomaterials

Abstract: Although there have been extensive research efforts to create functional tissues and organs, most successes in tissue engineering have been limited to avascular or thin tissues. The major hurdle in development of more complex tissues lies in the formation of vascular networks capable of delivering oxygen and nutrients throughout the engineered constructs. Sufficient neovascularization in scaffold materials can be achieved through coordinated application of angiogenic factors with proper cell types in biomateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(55 citation statements)
references
References 101 publications
(101 reference statements)
1
54
0
Order By: Relevance
“…[4,94,233235] Recently, the use of microscale technologies has been proposed as a method of addressing a number of challenges associated with difficulties in making tissue constructs that mimic the function and appearance of tissues in the body. [15] To engineer hydrogels with microscale resolution, a number of techniques have been developed.…”
Section: Advanced Fabrication Methodsmentioning
confidence: 99%
“…[4,94,233235] Recently, the use of microscale technologies has been proposed as a method of addressing a number of challenges associated with difficulties in making tissue constructs that mimic the function and appearance of tissues in the body. [15] To engineer hydrogels with microscale resolution, a number of techniques have been developed.…”
Section: Advanced Fabrication Methodsmentioning
confidence: 99%
“…It has been shown that the lack of vascularization of tissue-engineered bones leads to hypoxia and cell death after implantation [3, 4] and that bone-regenerative capacity of bone marrow stromal cells is improved when those are transplanted into a bone defect model with endothelial cells [5]. Nowadays, several strategies for enhancing vascularization are under investigation [6]. They include scaffold designed to promote angiogenesis [7, 8], in vitro prevascularization [912], and inclusion of angiogenic factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…These include using angiogenesis-inductive materials, incorporation of growth factors (either by conjugation, encapsulation, or supplementing), utilizing co-culture techniques, and using decellularized organs and blood vessels for creating ECM. The scaffold (made from vascular inductive materials) provides physical, chemical, and biological cues to control cell-matrix interactions and cellular processes such as angiogenesis [ 34 ]. Strategy to fabricate vascularized structures includes culturing cell-seeded porous polymeric scaffold in a bioreactor and implanting it in vivo to facilitate remodeling and integration with the host vascular network.…”
Section: Current Approaches For Engineering Complex Vascularized Tissuesmentioning
confidence: 99%